2021
DOI: 10.3389/fendo.2020.622950
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Knockout Inhibits Senescence of Bone Mesenchymal Stem Cells in High-Fat Diet-Induced Bone Loss

Abstract: Obesity, a chronic low-grade inflammatory state, not only promotes bone loss, but also accelerates cell senescence. However, little is known about the mechanisms that link obesity, bone loss, and cell senescence. Interleukin-6 (IL-6), a pivotal inflammatory mediator increased during obesity, is a candidate for promoting cell senescence and an important part of senescence-associated secretory phenotype (SASP). Here, wild type (WT) and (IL-6 KO) mice were fed with high-fat diet (HFD) for 12 weeks. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…Forward (5’) Pr8 NP: CAGCCTAATCAGACCAAATG, Reverse (3’): TACCTGCTTCTCAGTTCAAG. Forward (5’) β-Actin AGATTACTGCTCTGGCTCCTAGC and Reverse (3’): ACTCATCGTACTCCTGCTTGCT (Garcia et al, 2020; Li et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward (5’) Pr8 NP: CAGCCTAATCAGACCAAATG, Reverse (3’): TACCTGCTTCTCAGTTCAAG. Forward (5’) β-Actin AGATTACTGCTCTGGCTCCTAGC and Reverse (3’): ACTCATCGTACTCCTGCTTGCT (Garcia et al, 2020; Li et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The influenza dose used in these studies was previously described (Pardi et al, 2018a;Zens et al, 2016), while the SARS-CoV-2 dose was determined in house using hACE-2 mice (Suppl. ACTCATCGTACTCCTGCTTGCT (Garcia et al, 2020;Li et al, 2021).…”
Section: Intranasal Challenge With Pr8 Influenza and Sars-cov-2mentioning
confidence: 99%
“…152 However, recent studies have found that excess dietary fat intake can disrupt bone remodeling, can accelerate bone aging, and is an independent and controllable risk factor for osteoporosis. [153][154][155] A HFD induces chronic low-grade inflammation concomitant with an increase in the levels of pro-inflammatory cytokines (IL-1, IL-6, and TNFα), 156,157 aggravates oxidative stress, 158 affects the bone marrow microenvironment, and ultimately shifts the osteoblastic/ adipogenic differentiation balance among BMSCs. 21 This not only reduces the formation and differentiation of osteoblasts but also leads to the accumulation of BMAs, which inhibit osteoblast generation and promote osteoclast differentiation via leptin and adiponectin.…”
Section: Improper Diet the Gm And Bone Metabolismmentioning
confidence: 99%
“…Traditionally, a HFD was believed to be beneficial for bone health because it often leads to weight gain, and high body weight is widely considered to be a protective factor for bone health 152 . However, recent studies have found that excess dietary fat intake can disrupt bone remodeling, can accelerate bone aging, and is an independent and controllable risk factor for osteoporosis 153‐155 . A HFD induces chronic low‐grade inflammation concomitant with an increase in the levels of pro‐inflammatory cytokines (IL‐1, IL‐6, and TNF‐α), 156,157 aggravates oxidative stress, 158 affects the bone marrow microenvironment, and ultimately shifts the osteoblastic/adipogenic differentiation balance among BMSCs 21 .…”
Section: Improper Diet the Gm And Bone Metabolismmentioning
confidence: 99%
“…Accumulating studies have revealed osteogenesis downregulation [9], fatty marrow, bone mass loss [10], and biomechanical property repression [11] in mice upon HFD feeding. Oxidative stress [12], inflammatory cytokine overproduction [13], and Wnt signaling loss [14] aggravate the development of HFD-induced bone loss. In addition, epigenetic pathways, including histone lysine demethylase [15], RNA demethylase [16], and long non-coding RNA, in osteogenic cells [17] regulates HFD-induced bone mass loss and peripheral fat metabolism.…”
Section: Introductionmentioning
confidence: 99%